Emerging Technology: Cloud Computing for Enhanced Resource Accessibility - A Review - N.B.S Vijay Kumar, Dr.M Paul Daniel, K.John Paul,Daggubati Sunil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Cloud computing has rapidly emerged as a transformative technology that offers significant benefits to individuals, businesses, and institutions by providing efficient and flexible access to computing resources. This review paper aims to provide an in-depth analysis of the current state of cloud computing as an emerging technology, focusing on its impact on resource accessibility. Through a comprehensive examination of relevant literature, this paper explores the various aspects of cloud computing that contribute to improved resource accessibility, including scalability, cost-effectiveness, security, and the challenges associated with adoption. By synthesizing insights from diverse sources, this review paper offers a comprehensive understanding of the potential and challenges of cloud computing in revolutionizing resource access.